Systena nitentula (Coleoptera: Chrysomelidae), a flea beetle injurious to Alternanthera philoxeroides (Amaranthaceae): Redescription, biology, and distribution - Cabrera, Nora Clara (2005)
Flea beetles of alligator weed, Alternanthera philoxeroides (Martius) Grisebach (Amaranthaceae), were collected in Argentina, Uruguay, Paraguay, and Brazil. Species in the genera Disonycha Chevrolat, Agasicles Jacoby, and Systena Chevrolat were frequently found on this weed. Systena nitentula Bechyné 1954 was the most abundant within Systena. This species is reported for the first time from Argentina at north of 30° S. The male is described and holotype female is redescribed adding new diagnostic characters: mouthparts, hind wings, metendosternite, and male and female genitalia. S. nitentula is recognized by the combined characters of piceous elytra with J-shaped vittae, a small spermatheca pump, and internal median lobe sac with five sclerotized plates. Differences in color patterns between S. nitentula, S. tenuis Bechyné, and S. s-littera L. also are considered. S. nitentula presents three instars that can be separated through head width. New biological data based on laboratory rearing and field observations shows that S. nitentula could be a monophagous species strongly associated to the alligator weed growing in terrestrial conditions. This information promotes S. nitentula as a potential biocontrol agent of this invasive weed.